RESPONSIBLE FINANCE AND FINANCIAL LITERACY - LOBEZ, Frédéric (Bankers, Markets & Investors, 2023)
This article examines the financial education needed to achieve responsible finance. Responsibility here is considered in the broadest sense, i.e. towards company stakeholders, but also towards society and future generations. Given that finance is not only a social science and that it also includes a moral dimension, we first argue for a minimum financial education for all citizens, a condition for inclusive finance. We then outline some major changes that are intended to structure responsible financial education. The conclusions drawn concern academics and researchers working in finance as well as managers of financial institutions.